Case Report: Differentiating hepatic desmoplastic small round cell tumor from hydatidosis in a school-aged boy: the role of contrast-enhanced and interventional ultrasound - Gou, Zehui; Yan, Hualin; Yu, Boyang; Xie, Xiaolong; Xiang, Bo; Liu, Juxian; Luo, Yan (Frontiers in Oncology, 2025)
BackgroundDesmoplastic small round cell tumor (DSRCT) is a rare and highly aggressive malignant neoplasm, typically associated with poor prognosis. It predominantly affects adolescents and young males, with a lower incidence in pediatric populations. Due to its rarity, our understanding of DSRCT remains limited, with only a small number of case reports available. The clinical presentation is often non-specific and varies depending on the extent of tumor invasion. Diagnosis relies primarily on histopathological evaluation through biopsy. Although imaging studies contribute to the diagnostic process, they often lack specificity. Nonetheless, certain imaging features can aid in refining differential diagnoses and assessing disease severity. Moreover, minimally invasive, image-guided tissue sampling plays a critical role in confirming the diagnosis through pathological analysis.Case presentationA 7-year-old boy presented with abdominal distension and anorexia, without significant abdominal pain, fever, or jaundice. Physical examination revealed abdominal enlargement with hepatosplenomegaly. Laboratory tests showed abnormal liver function (AST 128 U/L, ALP 648 U/L, GGT 885 U/L) and an elevated CA-125 level (170 U/ml). An abdominal CT scan performed at a local hospital identified multiple round, low-density lesions in the liver, suggestive of echinococcosis. The patient was initially diagnosed with suspected echinococcosis and started on albendazole; however, his symptoms did not improve. Upon further evaluation at our institution, ultrasound imaging revealed multiple thick-walled, hyperechoic lesions in the liver with no significant blood flow signals. Contrast-enhanced ultrasound demonstrated that the solid components of the lesion exhibited significant enhancement during the early arterial phase, with rapid attenuation during the early portal venous phase. A metastatic malignant tumor was suspected, prompting a percutaneous biopsy under real-time enhanced ultrasound guidance. Histopathological examination revealed small round tumor cells infiltrating adjacent tissues. Fluorescence in situ hybridization (FISH) confirmed the diagnosis of DSRCT, based on the presence of an EWSR1-WT1 rearrangement. The patient subsequently underwent multimodal treatment, including chemotherapy and radiation therapy, and achieved disease-free survival at the six-month follow-up.ConclusionsTraditional ultrasound is a convenient, real-time, non-invasive, and radiation-free diagnostic tool, making it particularly well-suited for the diagnosis, screening, and clinical follow-up of focal liver lesions (FLLs) in pediatric patients. This modality enables real-time evaluation of the number, size, location, and morphology of FLLs while assisting in the differential diagnosis. Moreover, it facilitates the assessment of liver parenchyma involvement and portal vein structures. Color Doppler imaging provides valuable insights into the vascular characteristics of tumors, while contrast-enhanced ultrasound (CEUS) agents allow for real-time observation of dynamic tumor perfusion patterns, further refining differential diagnoses based on perfusion characteristics. Compared to the contrast agents used in CT or MRI—which may require sedation or carry risks of renal injury due to radiation exposure—ultrasound microbubble contrast agents are excreted via respiration and do not require sedation, making them especially suitable for pediatric patients. Additionally, ultrasound-guided biopsy is a well-established and reliable method for diagnosing liver lesions. However, the presence of extensive necrosis and the use of fine-needle biopsy can sometimes limit diagnostic accuracy. Incorporating CEUS before or during percutaneous biopsy can help optimize sampling site selection, thereby reducing the likelihood of false-negative results.